1977
DOI: 10.1203/00006450-197712000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Improved Micellar Dispersal of Dietary Lipid by Bile Acids during Replacement Therapy in Growth Hormone-deficient Children

Abstract: P e d i a t . R c s . 12: I 186-1 191 ( 1 0 7 7 ) Bile acids fat digestion g r o w t h h o r m o n e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Hypothyroidism secondary to TSH deficiency results in elevation of indirect bilirubin levels due to failure of conjugation in the absence of increased hemolysis. Corticosteroids have been reported to increase the enterohepatic circulation of bile salts (17). * Performed in J. M .…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism secondary to TSH deficiency results in elevation of indirect bilirubin levels due to failure of conjugation in the absence of increased hemolysis. Corticosteroids have been reported to increase the enterohepatic circulation of bile salts (17). * Performed in J. M .…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial report of CPHD in an infant with cholestasis and hypoglycemia by Blizzard and Alberts (7), several descriptions of case reports and few case series have been described. Although it is not exactly known how hormone deficiencies cause cholestasis, the evidence of clinical and some experimental data supports the role of pituitary trophic hormones (cortisol, GH and thyroid hormones) in the pathogenesis of this disorder (8)(9)(10)(11)(12)(13). Cortisol deficiency in adrenalectomized animals reduces biliary flow, which is reverted after treatment with hydrocortisone.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol deficiency in adrenalectomized animals reduces biliary flow, which is reverted after treatment with hydrocortisone. GH also modulates the biosynthesis and secretion of biliary acids, and it has been shown that biliary flow recovers after hydrocortisone and GH treatment (13)(14)(15). While there is not a pathognomonic biochemical pattern of liver dysfunction in relation to a particular hormone insufficiency, some reports have attempted to identify a pattern that leads towards this diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine weitere Beobachtung an Ratten zeigt, dass Wachstumshormon die Gallensäuresynthese modulieren kann [2]. Unter hGH-Therapie kommt es zu vermehrten Gallesäuremizellen im Jejunum [15]. …”
Section: Introductionunclassified